AirPrint Forensics: Recovering the Contents and Metadata of Printed Documents from iOS Devices - Gómez-Miralles, Luis; Arnedo-Moreno, Joan (Mobile information systems, 2015)
Since its presentation by Apple, both the iPhone and iPad devices have achieved great success and gained widespread popularity. This fact, added to the given idiosyncrasies of these new portable devices and the kind ofdata they may store, opens new opportunities in the field of computer forensics. In 2010, version 4 of the iOS operating system introduced AirPrint, a simple and driverless wireless printing functionality supported by hundreds of printer models from all major vendors. This paper describes the traces left in the iOS device when AirPrint is used and presents a method for recovering content and metadata of documents that have been printed.